Crystal Structure and Electrical Properties of Lead‐Free (1 − x)BaTiO3–x(Bi1/2A1/2)TiO3 (A = Ag, Li, Na, K, Rb, Cs) Ceramics. Issue 11 (7th August 2013) - Liu, Xiaoming; Tan, Xiaoli
Abstract : Ceramics of solid solutions (1 −   x )BaTiO3 – x (Bi1/2 A1/2 )TiO3 (A = Ag, Li, Na, K, Rb, Cs, x  ≤   0.20) were prepared and their crystal structures, dielectric, ferroelectric, and piezoelectric properties were investigated. It was found that (Bi1/2 A1/2 )TiO3 ‐type doping compounds broadened the temperature range of the tetragonal phase in BaTiO3 and all the compositions examined displayed a tetragonal structure at room temperature. The Curie temperature ( T C ) was observed to increase with respect to pure BaTiO3 to the range 140°C–210°C through solid solution. Remanent polarization ( P r ) tended to decrease with increased content of doping compound, whereas the coercive field ( E C ) rose and piezoelectric coefficient ( d 33 ) fell. The highest d 33 value in the solid solutions was observed in 0.97BaTiO3 –0.03(Bi1/2 Ag1/2 )TiO3 at 90 pC/N.